The liturgical year - Guéranger, Prosper 1805-1875; Fromage, Lucien 1845-1916.; Shepherd, James Laurence 1825-1885.; University of North Carolina at Chapel Hill (Dublin J. Duffy, 1867)
v. 1. Advent -- v. 2-3. Christmas -- v. 4. Septuagesima -- v. 5. Lent -- v. 6. Passiontide and Holy week -- v. 7-9. Paschal time -- v. 10-15. Time after Pentecost.
The last 6 volumes of the original French edition, published after Guéranger's death, are the work of Lucien Fromage. - Editions vary
Keywords: Catholic Church -- Liturgy; Church Year; Catholic Church